LA PRUEBA DE OFICIO EN EL PROCESO DE AMPARO AMBIENTAL - Grados Vega, Grobert Yampier (2018)
The objective of this research work was to determine the way in which the ex officio evidence provided by the Peruvian Constitutional Court contributes to the effectiveness of the amparo process in environmental matters. Due to the precarious regulation of the proof ex officio in the Constitutional Procedural Code, as well as the little doctrinal development of the subject, we have resorted to the general doctrine of ex officio proof and to the regulation that makes it the Civil Procedure Code to unravel the aspects that are applicable to the amparo process. Likewise, the jurisprudence of the Constitutional Court in environmental matters has contributed to highlight the particular characteristics of the fundamental right to the environment, as well as the influence of this in the configuration of the environmental protection process, which requires the establishment of special rules in its processing and resolution. In the present investigation it has been possible to determine that the Constitutional Court in most of the environmental protection proceedings in which it has the application of the ex officio evidence, does so assuming wrong criteria, such as that it can order the judge of first instance to exercise its probative powers, and how to directly exercise its own probative powers but violating the exceptionality limit, criteria that do not contribute to the effective protection of the fundamental right to the environment, since they violate the right of defense, and generate unnecessary, unjustified and exaggerated delays in the process, which can trigger irreparable damage.